Septoplasty in Pediatric Population: A Ten Years’ Experience - Koirala, Krishna Prasad (Birat Journal of Health Sciences, 2020)
Introduction: Septoplasty is a commonly performed surgical procedure worldwide in otorhinolaryngology. Septoplasty aims to correct the deviated nasal septum at the midline thereby opening the nasal airway in patients with long standing nasal obstruction secondary to septal deviation. Nasal breathing is important for proper facial growth and improvement of quality of life in children. Most surgeons are still reluctant to perform septoplasty in children. But septoplasty should be performed in children if there are severe breathing problems related to septal deviation. Objectives: The objectives of this study were to identify the incidence of children presenting with symptomatic nasal septal deviation and to analyze the early outcomes of septal surgery in children with regard to improvement in nasal symptoms, residual disease and need for revision surgery. Methodology: Children less than seventeen years of age who underwent septoplasty for symptomatic DNS from 1st January 2009 to 31st December 2018 were enrolled in the study. Patients having the follow up record of at least 6 months after surgery were included in the final analysis. Results: There were 37 male and 13 female children enrolled in the study. Male to female ratio was 2.84:1.Majority of children in the study were of 13 years (24%). Left sided DNS was seen in 28 children and right sided DNS in 22 children. Bleeding requiring re-packing, septal hematoma, recurrent DNS, synechia and septal perforation were the common complications, which were comparable to adult population. Conclusion: Early correction of the obstructed nose due to deviated nasal septum is essential to provide normal nasal breathing, relieve complications of mouth breathing and to promote normal craniofacial growth. Septoplasty can be performed in pediatric population with relatively good results without occurrence of nasal deformity and equal complications as that in adults.